A High Fidelity Cleft Lip Simulator. Issue 9 (September 2018) - Podolsky, Dale J.; Wong Riff, Karen W.; Drake, James M.; Forrest, Christopher R.; Fisher, David M.
Abstract : Background: Cleft lip surgery is technically difficult requiring precise planning and understanding of 3-dimensional structures to obtain an optimal outcome. A physical cleft lip simulator was developed that allows trainees to gain experience in cleft lip repair and primary rhinoplasty before operating on real patients. Methods: A cleft lip simulator that comprises multilayered soft tissues, bone, and realistic dissection planes was developed using 3D printing, adhesive and polymer techniques. Four experienced cleft surgeons performed a total of 7 simulated repairs on the simulator. Feedback on the realism and value of the simulator was obtained from the surgeons. Results: Six of the repairs were a Fisher anatomic subunit approximation technique, and 1 was a rotation advancement repair. All repairs were completed with successful performance of markings, incisions, dissections, and multilayered closure. All surgeons agreed that the simulator is realistic and that the simulator is a valuable tool for training in cleft lip surgery. Conclusions: A cleft lip simulator that allows performance of a cleft lip repair and primary rhinoplasty from start to finish was developed and pilot tested. The simulator provides a training platform to gain experience in cleft lip repair before operating on real patients. Abstract : Supplemental Digital Content is available in the text.